Analysis of Leadership, Work Discipline and Job Satisfaction on Employee Performance at CV Yudi Putra - Yesika Sari; Rahayu, Sri; Hasibuan, Hasrul Azwar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted at CV Yudi Putra to analyze the influence of leadership, discipline, and job satisfaction on employee performance. The sample consisted of 44 employees from a total population of 45 people including employees and leaders. The data used included primary and secondary data, collected through field research, field assessments, and observations. The analysis was conducted using multiple linear regression, classical assumption tests, and hypothesis tests (t-test and f-test). The results showed that leadership (X1) and discipline (X2) had a significant positive impact on employee performance, while job satisfaction (X3) had a positive but insignificant effect. Simultaneously, leadership, discipline, and job satisfaction affected employee performance with the results of the F test showing a significant effect. The correlation between the three variables and employee performance reached 58%, while 42% was influenced by other factors such as training, compensation, and work stress